2017
DOI: 10.1371/journal.pone.0175534
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement intervention to increase adherence to ART prescription policy at HIV treatment clinics in Lusaka, Zambia: A cluster randomized trial

Abstract: IntroductionIn urban areas, crowded HIV treatment facilities with long patient wait times can deter patients from attending their clinical appointments and picking up their medications, ultimately disrupting patient care and compromising patient retention and adherence.MethodsFormative research at eight facilities in Lusaka revealed that only 46% of stable HIV treatment patients were receiving a three-month refill supply of antiretroviral drugs, despite it being national policy for stable adult patients. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Similar findings of better service readiness in hospitals compared to primary care facilities is evident in other settings as well [33,45]. Studies have shown that healthcare utilization patterns, retention in care and people's decision to bypass facilities is due to the patient's perception of quality [46,47]. In Nepal [48], India [15,49] and some sub-Saharan Africa countries [50,51], bypassing the nearest public health facility for a higher level facility or private facility due to at least one quality concern is evident.…”
Section: Discussionmentioning
confidence: 62%
“…Similar findings of better service readiness in hospitals compared to primary care facilities is evident in other settings as well [33,45]. Studies have shown that healthcare utilization patterns, retention in care and people's decision to bypass facilities is due to the patient's perception of quality [46,47]. In Nepal [48], India [15,49] and some sub-Saharan Africa countries [50,51], bypassing the nearest public health facility for a higher level facility or private facility due to at least one quality concern is evident.…”
Section: Discussionmentioning
confidence: 62%
“…In Ethiopia, 6-month refills have been rolled out with initial positive findings [33]. A quality improvement intervention from Zambia increased the number of facilities offering 3-month refills in accordance with national policy, which resulted in 20 fewer patient visits per day in facilities receiving the intervention [34]. Since April 2019, following a Ministry of Health directive, Zambia also has scaled up 6-month refills for stable patients.…”
Section: Antiretroviral Delivery For Stable Clientsmentioning
confidence: 99%
“…By leveraging a four-step continuous cycle of improvement (plan-do-check-act), these programmes have driven substantive change by developing local solutions to improve the quality of HIV care. Improvements have been shown across different facets of care, including treatment adherence, 136 reducing mother-to-child transmission of HIV, 137 paediatric services, 138 enhancing adherence to treatment guidelines, 139 and strengthening the clinical capacity of front-line providers. 140 Similar approaches can be used to improve the quality of care for patients with tuberculosis, while also enabling increased accountability at all levels of national tuberculosis programmes (case studies in the appendix pp 22-24 provide examples from the public and private sector, at facility and regional level, of how quality improvement approaches have been deployed to improve tuberculosis outcomes).…”
Section: Implementing Quality Improvement: Lessons Learned From Tacklmentioning
confidence: 99%